Ekspresi HER-2 pada Adenokarsinoma Gaster dan Hubungannya dengan Tipe Histopatologik dan Derajat Diferensiasi - Diah Setiawati; Diah Rini Handjari; Primariadewi Rustamadji (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2015)
Background Gastric carcinoma is the most common malignant tumor in upper gastrointestinal. According to epidemiologic data, gastric adenocarcinoma intestinal type and diffuse type showed different carcinogenesis. Recently, targeting therapy for adenocarcinoma has established. The aim of the study to know the relationship between HER-2 expression and histopathologic type according to Lauren’s classification and grading of gastric adenocarcinoma. Methods This study has done in Department of Anatomical Pathology Faculty of Medicine University of Indonesia/Cipto Mangunkusumo National Hospital, Jakarta. HER-2 expression is analyzed to see the relationship with histopathologic type and differentiation of gastric adenocarcinoma. The specimens were from resection and biopsy (2007-2011). Histopathologic type evaluated with Hematoxylin Meyer’s staining. HER-2 expression evaluated with immunostaining with HER-2 antibody. Results We found 55 cases from 2007 until 2011 (76.4% men and 23.6% women). The mean age is 50.55 years (the range of age 29-73 years). HER-2 expression 3+,2+ and 1+ are 14.5%, 34.5%, and 25.5% sampling. 25% sample did not show HER-2 expression. We found overexpression HER-2 (3+) in 8 cases (14.5%) of adenocarcinoma gastric intestinal type. Conclusion There is a significant relation between HER-2 expression with histopathologic type (p=0.021). There is no significant relation between HER-2 with grading (p=0.253). Key words: grading, gastric adenocarcinoma, HER-2.